Tanabe Hajime’s God - Heisig, James W. (Bulletin of the Nanzan Institute for Religion & Culture, 2014)
The following is an expanded version of an essay prepared for the forthcoming “Oxford Handbook of Japanese Philosophy,” edited by Bret W. Davis, and is published here with their kind permission.